(untitled) (Bangladesh Journal of Medical Science, 2014)
Neonatal infection is an important cause of morbidity and mortality among infants. Clinical pattern of neonatal infection in the neonatal unit of Institute of Post Graduate Medicine & Research (IPGM&R), Dhaka has been reported. Out of total 2160 Neonatal admission from July 1991 to June 1993, 320 (14.8%) cases of neonatal infections were found. Septicemia was the commonest type found in 118 (5.5%) cases. Other infections included umbilical sepsis (14.7%), Skin infections (1.6%), Meningitis (1.2%). Tetanus neonatorum were not included. Out of 320 cases, 20 patients died (6.2%). Preterm low birth weight and birth asphyxia were the common risk factors. DOI: http://dx.doi.org/10.3329.bjms.v1i3.17909